A longitudinal investigation of parental social-economic status (SES) and young students' learning of English as a foreign language. (April 2018) - Butler, Yuko Goto; Le, Vi-Nhuan
Abstract: Despite the growing tendency worldwide to lower the starting age of English education, our knowledge of how young students learn English over time remains limited. Particularly limited is our knowledge of how parental socio-economic status (SES) influences their children's English learning. This study investigated the role of parental SES in Chinese middle school students' English learning over time. The participants were 189 middle school students and their parents who were drawn from two distinct socioeconomic areas. Students were followed for three years from the seventh to ninth grade (ranging in age from 12 to 15). Each year, students took the Cambridge ESOL tests and filled out surveys concerning their English learning and motivation. Their parents also filled out extensive surveys regarding family background, resources, and parenting styles and beliefs. We found significant relationships between SES and parents' attitudes towards the role of English, parenting styles, Chinese books available at home, parental involvement in children's English learning, and parental beliefs and expectations toward their children's English learning ability. We also found that SES, parenting styles (autonomous style rather than controlled style), and parental beliefs and expectations were positively associated with students' English performance.